2014
DOI: 10.1179/1756750514z.00000000053
|View full text |Cite
|
Sign up to set email alerts
|

Building with History: Exploring the Relationship between Heritage and Energy in Institutionally Managed Buildings

Abstract: Drawing on interdisciplinary research focusing on Durham University estate, we describe how buildings constructed as part of an eighteenth century transition to a high carbon coal-based economy, are used and understood by their current inhabitants. Applied heritage research has tended to focus on the thermal and energetic properties of historic buildings, as distinct from their social meaning and use. A similar separation between the physical building and its social use is inherent in methodologies such as ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…While the need for a CE approach to ARCH is clear, the choice of which environmental indicators should be used as management tools to implement CE, is not. Closing this gap is vital because a lack of awareness and a lack of practical advice are barriers to implementing CE strategies for buildings, particularly ARCH [4,25].…”
Section: "Circular Economy Is a Production And Consumption Process Thmentioning
confidence: 99%
“…While the need for a CE approach to ARCH is clear, the choice of which environmental indicators should be used as management tools to implement CE, is not. Closing this gap is vital because a lack of awareness and a lack of practical advice are barriers to implementing CE strategies for buildings, particularly ARCH [4,25].…”
Section: "Circular Economy Is a Production And Consumption Process Thmentioning
confidence: 99%
“…Explicitly articulated heritage values support a more informed selection process (Lidelöw et al 2019). As Adams et al (2014) pointed out, "by increasing awareness of the historic features of these buildings, specifically as they relate to energy use, it might be possible to engender attitudes that promote more effective use of the infrastructural legacies of the past" (p. 179).…”
Section: Graphical Representation Of Energy Efficiency Targets In Historic Buildingsmentioning
confidence: 99%
“…Of course, one of the first aspects to investigate is if (and how) occupants’ comfort perception and behaviour is different in historical buildings. One of the few studies made regarding occupants’ comfort perception in historic buildings, which took into account historic residences in the UK, demonstrated that the awareness of the historic value of the building can affect users’ evaluation of comfort (Charlotte et al ., 2014). Regarding behaviour, Ben and Steemers (2014) found that, in their sample of historic residences, the impact of behavioural change consequent to education activities exceeds the efficacy of physical improvement of the historic fabric.…”
Section: Energy Performances Of Historical Buildingsmentioning
confidence: 99%